Morphologic And Morphometric Evaluation of Acetabulum of Hip Bone Among North Indian Population - Khurana, Sanya; Lal, Nidhi; Saha, Susmita; Aneja, Prachi Saffar; Yadav, Jahanvi; Sharma, Yamini (Journal of Neonatal Surgery, 2025)
Background: Acetabulum is a deep cup-shaped cavity present on the lateral side of hip bone, where three small bones unite and fuse. It articulates with femoral head to form hip joint, a ball and socket variety of synovial joint. Acetabular cavity is divided into two parts: articular lunate surface and non-articular rough acetabular fossa. To design prosthesis in hip arthroplasty and for total hip replacement surgeries, knowledge of detailed morphometry and morphology of acetabulum is needed for orthopaedic surgeons. Methods: Present observational study was conducted on 56 dry human hip bones of both sexes from the bone bank, Department of Anatomy, FMHS, SGT University, Gurugram, Haryana. Detailed morphometry of acetabulum including non-articular acetabular fossa and lunate surface was carried out with the help of digital vernier calliper whereas morphological features were observed by visual inspection. Statistical analysis was performed by SPSS software latest version (version 21) to find mean, standard deviation along with p value and t value for bilateral comparison. Results and discussion: Mean transverse and vertical diameter of acetabulum on right side was 46.81 ± 3.64 mm and 52.86 ± 3.89 mm and 47.14±3.21mm and 52.73 ± 3.84 mm on left side respectively. Mean values of depth of acetabulum and width of acetabular notch was 24.07 ± 1.89 mm and 22.14 ± 4.32 mm on the right side and 24.22 ± 2.16 mm and 25.28 ± 5.77 mm on the left side respectively. Average values of transverse and vertical diameter of non-articular part of acetabular fossa was 28.33 ± 2.82 mm and 35.11 ± 2.57 mm on right side and 28.29 ± 2.47mm and 34.83 ± 3.75 mm on left side respectively. Incidence of lunate shape of lunate surface at the posterior end was the maximum (91.1%) and curved shape of anterior acetabular ridge was the most common (42.9%). Significant bilateral asymmetry in the anterior end morphology of the lunate surface (p < 0.05) found. No significant side preference in shape distribution of the anterior acetabular ridge seen. There are strong correlations between right and left measurements of main diameters of acetabulum. Width of acetabular notch shows significant bilateral difference, left side showing greater variability. Conclusions: The data provides a detailed evaluation of morphometry and morphology of acetabulum, which is of immense help to orthopaedic surgeons for prosthesis design in hip arthroplasty. It will also enhance knowledge among radiologists in diagnosing pathological condition such as femoro-acetabular impingement.